2009
DOI: 10.1007/s11104-009-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 induces differences in nodulation of soybean depending on bradyrhizobial strain and method of inoculation

Abstract: High CO 2 has been shown to increase plant growth and to affect symbiotic activity in many legumes species, including soybean (Glycine max [L.] Merr.). In order to assess the interaction between elevated CO 2 and rhizobial symbionts on soybean growth and nodulation, we combined the effects of CO 2 with those of different bradyrhizobial strains and methods of inoculation. Soybean seeds were sown in agricultural soil in pots and inoculated with three strains of Bradyrhizobium japonicum (5Sc2 and 12NS14 indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…2) showed that 96 out of 143 OTUs significantly enriched in the endosphere under eCO 2 conditions belonged to N 2 fixing bacteria, including unclassified members of Rhizobiales and Burkholderiaceae. This finding also corresponds to previous results showing that eCO 2 stimulated increases in both the mass and number of soybean nodules, along with a 33% increase in shoot C and a 78% increase in N uptake 57 .…”
Section: Discussionsupporting
confidence: 92%
“…2) showed that 96 out of 143 OTUs significantly enriched in the endosphere under eCO 2 conditions belonged to N 2 fixing bacteria, including unclassified members of Rhizobiales and Burkholderiaceae. This finding also corresponds to previous results showing that eCO 2 stimulated increases in both the mass and number of soybean nodules, along with a 33% increase in shoot C and a 78% increase in N uptake 57 .…”
Section: Discussionsupporting
confidence: 92%
“…Others also reported that the C/N ratio of soybean straw at maturity was unaffected by elevated [CO 2 ] Torbert et al 2004), although higher C/N ratio in fully expanded leaf was observed under elevated [CO 2 ] at vegetative and reproductive stages of soybean (Ainsworth et al 2007). The increases in C accumulation (17%; p<0.05) and N uptake (21%; p<0.05) of the above-ground parts of soybean under CO 2 enrichment (Table 1) are consistent with Prévost et al (2010).…”
Section: Resultssupporting
confidence: 76%
“…Although alteration of the carbon supply due to enhanced CO 2 fixation rates has been postulated to directly influence nitrogen cycling in soils ( 21 ), the influence of this greenhouse gas on the nitrogen-fixing symbiosis between B. japonicum and soybean is poorly understood. Recently, however, Prévost et al ( 38 ) reported that elevated atmospheric CO 2 increased soybean nodule number and mass, and increased shoot dry weight, and C and N uptake compared to ambient CO 2 . The reasons, however, for the reported CO 2 -induced enhancement of the symbiosis are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The biomass of several legumes species, including Acacia species, alfalfa ( Medicago sativa ), and mungbean ( Vigna radiata ), have been shown to increase under conditions of elevated CO 2 , and increased plant growth has sometime been correlated with enhanced nodulation and nitrogenase activity ( 7 , 50 ). Elevated atmospheric CO 2 has also been shown to increase nitrogen fixation activity and nodulation of Bradyrhizobium in symbiosis with soybean ( Glycine max ) ( 38 ) and dry matter production by 50% ( 2 ).…”
mentioning
confidence: 99%